Perfil químico e sensorial de grãos de diferentes genótipos de coffea canephora - Machado, Jéssica Louzada (2019)
The quality of the coffee is related to the characteristics of the flavor and aroma developed during the roasting. These characteristics are influenced by the chemical composition of the grains that can vary with the place of cultivation, genetic variety,